Analisis Perbandingan Kualitas Dan Kecepatan Transfer Data Pada Penggunaan Smartphone - Natasa, Sara; Khair, Ummul; Wulan, Nur (Teknik Informatika, Universitas Pelita Bangsa, 2023)
Along with the rapid development of technology makes the process of sending communication data faster. Data transfer or data communication is the exchange of data between two or more devices through a transmission medium such as cable or wireless. Data communication can also be defined as a process of sending and receiving data electronically from two or more devices connected to a network via a medium. This study aims to be able to compare the smartphones tested in testing the quality and speed of data transfer so as to produce comparative data between the four smartphones using the Telkomsel 4G LTE provider and each smartphone tested has a different storage space, different CPU and GPU. Different too. So that this test gets results where one of the smartphone tested has a very goog quality file received. Keywords: smartphone, 4G LTE, transfer data, Nperf, OneDrive dan kecepatan